Prevalence of arterial hypertension and risk factors among people with acquired immunodeficiency syndrome - Gilmara Holanda da Cunha; Maria Amanda Correia Lima; Marli Teresinha Gimeniz Galvão; Francisco Vagnaldo Fechine; Marina Soares Monteiro Fontenele; Larissa Rodrigues Siqueira (Universidade de São Paulo, 2018)
ABSTRACT Objectives: to verify the prevalence of arterial hypertension and its risk factors among people with acquired immunodeficiency syndrome under antiretroviral therapy. Method: cross-sectional study with 208 patients. Data collection was conducted through interviews using a form containing data on sociodemographic, clinical and epidemiological aspects, hypertension risk factors, blood pressure, weight, height, body mass index and abdominal circumference. Mean, standard deviation, odds ratio and confidence interval were calculated, t-test and Chi-square test were used, considering P < 0.05 as statistically significant. Hypertension associated variables were selected for logistic regression. Results: patients were male (70.7%), self-reported as mixed-race (68.2%), had schooling between 9 and 12 years of study (46.6%), had no children (47.6%), were single (44.2%), in the sexual exposure category (72.1%) and heterosexual (60.6%). The prevalence of people with acquired immunodeficiency syndrome and arterial hypertension was 17.3%. Logistic regression confirmed the influence of age greater than 45 years, family history of hypertension, being overweight and antiretroviral therapy for more than 36 months for hypertension to occur. Conclusion: the prevalence of hypertension was 17.3%. Patients with acquired immunodeficiency syndrome and hypertension were older than 45 years, had family history of hypertension, were overweight and under antiretroviral therapy for more than 36 months.